2020
DOI: 10.1037/fam0000727
|View full text |Cite
|
Sign up to set email alerts
|

Detouring in the family system as an antecedent of children’s adjustment problems.

Abstract: Guided by conceptualizations of relational boundaries from family systems theory, this study examined unique links between detouring (e.g., alliance between parents against child) and young children's psychological functioning after accounting for general family negativity and conflict. Participants in this longitudinal (i.e., 2 annual waves of data collection), multimethod (i.e., observation, survey, semistructured interview), multiinformant (i.e., parent, teacher, observer) study included 218 young children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, some other work has implied that the association between parent-child triangulation and child development may vary across the dimensions of triangulation and cultural contexts. Contrary to the compelling evidence on the adverse effect of cross-generational coalition and scapegoating on child adjustment (Coe et al, 2020 ; Wang et al, 2017 ), there have been mixed findings on the association between parentification and child adjustment. Some studies conducted in Western societies (Goldner et al, 2022 ; Pakenham & Cox, 2012 ) indicated that increased engagement in parentification was linked with poorer adjustment.…”
Section: Introductionmentioning
confidence: 89%
“…However, some other work has implied that the association between parent-child triangulation and child development may vary across the dimensions of triangulation and cultural contexts. Contrary to the compelling evidence on the adverse effect of cross-generational coalition and scapegoating on child adjustment (Coe et al, 2020 ; Wang et al, 2017 ), there have been mixed findings on the association between parentification and child adjustment. Some studies conducted in Western societies (Goldner et al, 2022 ; Pakenham & Cox, 2012 ) indicated that increased engagement in parentification was linked with poorer adjustment.…”
Section: Introductionmentioning
confidence: 89%
“…Parent-child relational boundaries were assessed from videotaped 15min observations of parent-child free play tasks. We adapted a family boundary observational rating system used in prior studies (Coe et al, 2018(Coe et al, , 2020 for use in the parent-child free play task. Using three 9point scales ranging from 1 ("not at all characteristic") to 9 ("highly characteristic"), the videotaped tasks were coded for the degree to which each parent-child dyad displayed cohesion, enmeshment, and disengagement (described below).…”
Section: Parent-child Relational Boundariesmentioning
confidence: 99%
“…Being triggered by the spouse's stresses or hostility, mothers may use maternal psychological control to safeguard the children's obedience towards them and/or relieve their tension (Gao et al, 2019). Under this situation, "scapegoating" (Yahav & Sharlin, 2002) or "detouring" (Coe et al, 2020) may happen. As studies on father-perceived marital dissatisfaction, detouring, scapegoating, and maternal psychological control are almost non-existent in the Chinese context, future research on this area is suggested.…”
Section: Marital Dissatisfaction and Psychological Controlmentioning
confidence: 99%
“…In the scientific literature, research examining the associations of marital qualities with parenting and parent-child relationship has been predominated by studies in the U.S. and Europe (e.g., Coe et al, 2020; Grych et al, 2004; Ponnet et al, 2013), while only very few studies have been conducted in Chinese societies (e.g., Chang et al, 2004; Shek, 2000). Based on the Confucian thoughts where familism is emphasized, family harmony, solidarity and prosperity are regarded as core values of Chinese families (Yeh & Yang, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation